Probiotics and Synbiotics: Applications, Benefits, and Mechanisms for the Improvement of Human and Ecological Health - Bhatia A; Sharma D; Mehta J; Kumarasamy V; Begum MY; Siddiqua A; Sekar M; Subramaniyan V; Wong LS; Mat Rani NNI (Journal of Multidisciplinary Healthcare)
Ankita Bhatia,1 Deeksha Sharma,1 Jyoti Mehta,1 Vinoth Kumarasamy,2 M Yasmin Begum,3 Ayesha Siddiqua,4 Mahendran Sekar,5 Vetriselvan Subramaniyan,6 Ling Shing Wong,7 Nur Najihah Izzati Mat Rani8 1Faculty of Applied Sciences and Biotechnology, Shoolini University of Biotechnology and Management Sciences, Solan, Himachal Pradesh, India; 2Department of Parasitology & Medical Entomology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Jalan Yaacob Latif, Cheras, Kuala Lumpur, Malaysia; 3Department of Pharmaceutics, College of Pharmacy, King Khalid University, Abha, Saudi Arabia; 4Department of Clinical Pharmacy, College of Pharmacy, King Khalid University, Abha, Saudi Arabia; 5School of Pharmacy, Monash University Malaysia, Bandar Sunway, Subang Jaya, Selangor, Malaysia; 6Department of Medical Sciences, School of Medical and Life Sciences, Sunway University, Bandar Sunway, Selangor, Malaysia; 7Faculty of Health and Life Sciences, INTI International University, Nilai, Malaysia; 8Faculty of Pharmacy and Health Sciences, Royal College of Medicine Perak, Universiti Kuala Lumpur, Ipoh, Perak, MalaysiaCorrespondence: Jyoti Mehta, Email yjjyoti@gmail.com; Vinoth Kumarasamy, Email vinoth@ukm.edu.myAbstract: This review explores the multifaceted roles and applications of probiotics, emphasizing their significance in maintaining and enhancing host health through microbial interactions. It includes the concept of holobionts and the symbiotic relationships between hosts and their microbiomes, illustrating how various microbiota can enhance immunity, support growth, and prevent diseases. It delves into the customization of probiotics using molecular and genomic techniques, focusing Enterococcus, Bifidobacterium, and Lactobacillus species. Furthermore, it discusses the symbiotic effects of symbiotics which aids in enhancing the survivability and beneficial effects of probiotics. The role beneficial microbes in gut is emphasized, noting its impact on preventing diseases and maintaining a stable microbial community. The potential therapeutic value of probiotics includes the ability to treat gastrointestinal diseases, as well as to strengthen the immune system and reduce the number of free radicals that are present in the body. Additionally, it explores secondary metabolites produced by bacteria in the gut, such as bacteriocins and exopolysaccharides, and their effect on the health of human, particularly in the gastrointestinal tract. The review concludes by addressing the use of probiotics in traditional medicine and their potential in novel therapeutic applications, including the treatment of endangered wildlife species and various human ailments.Keywords: human health, gut microbiota, secondary metabolites, synergistic effects